Prevalence and distribution of seven human pathogens in host-seeking Ixodes scapularis (Acari: Ixodidae) nymphs in Minnesota, USA - Johnson, Tammi L. (Ticks Tick Borne Dis, 2018)
In the north-central United States, the blacklegged tick (Ixodes scapularis) is currently known to vector seven human pathogens. These include five bacteria (Borrelia burgdorferi sensu stricto, Borrelia mayonii, Borrelia miyamotoi, Anaplasma phagocytophilum, Ehrlichia muris eauclairensis), one protozoan (Babesia microti) and one virus (Powassan). We sought to assess the prevalence and distribution of these pathogens in host-seeking nymphs collected throughout Minnesota, a state on the northwestern edge of the tick’s expanding range, where reported cases of I. scapularis-borne diseases have increased in incidence and geographic range over the past decade. Among the 1240 host-seeking I. scapularis nymphs that we screened from 64 sites, we detected all seven pathogens at varying frequencies. Borrelia burgdorferi s.s. was the most prevalent and geographically widespread, found in 25.24% of all nymphs tested. Anaplasma phagocytophilum and Babesia microti were also geographically widespread, but they were less prevalent than Bo. burgdorferi s.s. (detected in 6.29% and 4.68% of ticks, respectively). Spatial clusters of sites with high prevalence for these three pathogens were identified in the north-central region of the state. Prevalence was less than 1.29% for each of the remaining pathogens. Two or more pathogens were detected in 90 nymphs (7.26%); coinfections with Bo. burgdorferi s.s. and either A. phagocytophilum (51 nymphs, 4.11%) or Ba. microti (43 nymphs, 3.47%) were the most common combinations. The distribution and density of infected ticks mirrors the distribution of notifiable tick-borne diseases in Minnesota and provides information on the distribution and prevalence of recently described human pathogens.